Field testing the diagnostic criteria of cluster headache in the third edition of the International Classification of Headache Disorders: A cross-sectional multicentre study. (June 2019) - Moon, Heui-Soo; Cho, Soo-Jin; Kim, Byung-Kun; Lee, Mi Ji; Chung, Pil-Wook; Sohn, Jong-Hee; Kim, Soo-Kyoung; Choi, Yun-Ju; Song, Tae-Jin; Kim, Jae-Moon; Park, Jeong Wook; Park, Kwang-Yeol; et al.
Background: *These authors are shared first authors. The recently published third edition of the International Classification of Headache Disorders (ICHD-3) revised the criteria for accompanying symptoms of cluster headache (CH) and the remission period of chronic cluster headache (CCH). This study aimed at testing the validity of the ICHD-3 criteria for CH by using data from the Korean Cluster Headache Registry. Methods: Consecutive patients with CH and probable cluster headache (PCH) were prospectively recruited from 15 hospitals. We analysed the validity of the revised ICHD-3 criteria for CH against the beta version of the third edition of the ICHD (ICHD-3β). Results: In total, 193 patients were enrolled: 140 (72.5%), 5 (2.6%) and 22 (11.4%) had episodic cluster headache (ECH), CCH, and PCH, respectively. The remaining 26 (13.5%) had CH with undetermined remission periods. One patient with ECH and one with PCH had only forehead and facial flushing and were diagnosed with PCH and non-cluster headache, respectively, according to the ICHD-3. Four participants with ECH according to the ICHD-3β had remission periods of > 1 month and between 1 and 3 months and were newly diagnosed with CCH according to the ICHD-3. Conclusion: The change from ICHD-3β to ICHD-3 resulted in few differences in the diagnoses of CH and PCH.